Analisis Kelayakan Usaha Sayur Gulung Ditinjau dari Aspek Keuangan dan Non-Keuangan: Studi Pada Usaha Mahasiswa Universitas Slamet Riyadi Surakarta - Yuanita Putri Nurmalitasari; Marjam Desma Rahadhini (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the feasibility of the Sayur Gulung (SaGuMy) business run by students of Universitas Slamet Riyadi Surakarta, viewed from both financial and non-financial aspects. The non-financial aspects include production management, marketing, human resources, technical operations, and legal compliance. Meanwhile, the financial aspect is assessed through indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). This research employs a descriptive qualitative method combined with quantitative analysis using a case study approach. Data were collected through interviews, observations, and documentation, with data validity tested using source triangulation. In addition, quantitative analysis was applied to evaluate financial feasibility based on SaGuMy’s financial reports. The results indicate that the Sayur Gulung business is considered feasible to run. From the non-financial perspective, the business demonstrates an efficient production system, targeted marketing strategies, solid human resource management, adequate technical operations, and strong legal compliance. From the financial aspect, the business shows a positive NPV, an IRR exceeding the discount rate, a PP shorter than the standard payback period, and a PI greater than 1, all indicating financial viability. This study is expected to serve as a reference for student entrepreneurs and relevant stakeholders in assessing the feasibility of similar business ventures in academic environments